Analisis Administrasi Penyuluhan: Efektivitas BPP Dalam Diseminasi Inovasi Budidaya Padi Di Provinsi Sulawesi Selatan - Nurhayati; Raffi El Shirazy Achmad; Muhammad Subhan; Muhammad Nazli Syahma; Rhama Ady Pradiptha; Mutiah Ramadani Harahap; Riana Dwi Arianti (AGRINUS : Jurnal Agro Marin Nusantara, 2025)
Increasing rice production is the main pillar in realizing national food self-sufficiency. South Sulawesi Province, especially Sidenreng Rappang Regency (Sidrap), plays a strategic role as one of Indonesia's food barns. This paper aims to analyze the performance of the Agricultural Extension Center (BPP) in downstreaming rice cultivation technology and its impact on farmer productivity. Through the case study method, it was found that BPP plays a crucial role as a bridge of innovation between research institutions and farmers. The technology downstream strategy implemented includes the use of new superior varieties (VUB), legowo row planting system, balanced fertilization, and Integrated Pest Control (PHT). The results of the analysis show that despite the constraints in the form of capital limitations and resistance to changes in traditional methods, the intensive performance of extension workers through field assistance is able to significantly increase the efficiency of farming and production yields. In conclusion, strengthening the function of BPP and accelerating the adoption of mechanization technology is the main key in maintaining the sustainability of food self-sufficiency in South Sulawesi.